2014
DOI: 10.1158/0008-5472.can-13-2321
|View full text |Cite
|
Sign up to set email alerts
|

LEO1 Is Regulated by PRL-3 and Mediates Its Oncogenic Properties in Acute Myelogenous Leukemia

Abstract: PRL-3, an oncogenic dual-specificity phosphatase, is overexpressed in 50% of acute myelogenous leukemia (AML) and associated with poor survival. We found that stable expression of PRL-3 confers cytokine independence and growth advantage of AML cells. However, how PRL-3 mediates these functions in AML is not known. To comprehensively screen for PRL3-regulated proteins in AML, we performed SILAC-based quantitative proteomics analysis and discovered 398 significantly perturbed proteins after PRL-3 overexpression.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 29 publications
2
29
0
Order By: Relevance
“…Another type of proteomic screening or profiling where MS-based proteomics can reveal new biological insight and markers is over-expression or knock-down of oncogenes in cell lines followed by protein quantification of the induced biological activities, as demonstrated in a study of protein tyrosine phosphatase type IVA 3 (TP4A3) by Chong et al [107]. By screening the quantified proteins in the downstream signaling pathway of TP4A3, 398 proteins were significantly altered and RNA polymerase-associated protein Leo1 was identified as a novel mediator of the oncogenic functions of TP4A3 in leukemia.…”
Section: Proteomic Contributions To Unravel the Aml Proteomementioning
confidence: 99%
“…Another type of proteomic screening or profiling where MS-based proteomics can reveal new biological insight and markers is over-expression or knock-down of oncogenes in cell lines followed by protein quantification of the induced biological activities, as demonstrated in a study of protein tyrosine phosphatase type IVA 3 (TP4A3) by Chong et al [107]. By screening the quantified proteins in the downstream signaling pathway of TP4A3, 398 proteins were significantly altered and RNA polymerase-associated protein Leo1 was identified as a novel mediator of the oncogenic functions of TP4A3 in leukemia.…”
Section: Proteomic Contributions To Unravel the Aml Proteomementioning
confidence: 99%
“…PRL-3 also modulates gene transcription through the functional and/or physical associations with key transcriptional factors (10,1517). Moreover, the role of PRL-3 in epigenetic regulation was proposed, but the mechanism is unclear (18,19). In Xenopus laevis , lose-of-function and gain-of-function studies showed that PRL-3 is required for migration of cephalic neural crest cells during embryonic development (20).…”
Section: Introductionmentioning
confidence: 99%
“…As reported in previous studies (15,18), we established a pair of stable, isogenic cell lines, TF1-pEGFP and TF1-hPRL3, by transfecting pEGFP (vector control) and pEGFP-hPRL-3 vectors into TF-1 cells, respectively, and showed that PRL-3 promoted cytokine-independent growth of AML cells. Here, we further determined the in vivo function of PRL-3 on leukemogenesis by using this pair of TF1 cells in a bone marrow transplantation xenograft assay.…”
Section: Prl-3 Promotes Aml Maintenance and Progression In Vivomentioning
confidence: 80%
“…Importantly, several studies have independently confirmed that the high expression of PRL-3 is associated with poor survival in AML (15)(16)(17). We previously demonstrated that LEO1, a component of RNA polymerase IIassociated factor (PAF) complex, was induced by PRL-3 in AML (18). PAF complex plays an essential role in MLL-rearranged leukemia (19).…”
Section: Introductionmentioning
confidence: 92%